التعلم التنظيمي كأسلوب لتطوير الكفاءات والمهارات البشرية بالجامعة الجزائرية -دراسة حالة عينة من جامعات الشرق- - عمارة, سلمى; بوخضرة, مريم (جامعة الوادي University of Eloued, 2019)
This research paper highlights the new direction of management trends is the organizational learning and its importance in the development of competencies and human skills in the Algerian university, by relying on a sample of East universities, consisting of three universities.To obtain the necessary data and information was used questionnaire and analyzed through the use of SPSS program to test hypotheses and draw conclusions.The study results showed that there is a positive effect of organizational learning in the development of competencies and human skills in universities under study.
Organizational learning as a method to develop human competencies and skills at the Algerian University Case study of a sample of universities in the Eas
مقال
Keywords: التعلم التنظيمي، الكفاءات البشرية، المهارات البشرية، الجامعات الجزائرية.; Organizational learning, human competencies, human skills ,Algerian universities